ENTOMOLOGICAL INVESTIGATIONS IN MOULAY YAACOUB, LEISHMANIASIS FOCUS IN THE CENTR OF MOROCCO - KHADIJA LAHOUITI,; KHADIJA BEKHTI,; MOUHCINE FADIL,; ABDELHAKIM EL OUALI LALAMI, (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: In Morocco leishmaniasis represent entities of great clinical and epidemiological diversity and thus constitute a public health problem. The area of Moulay Yaâcoub, North central of Morocco. This study was conducted in all localities of the province of Moulay Yaâcoub to understand the epidemiology and spatial distribution of sandflies in this region. Nine among eleven localities of the province of Moulay Yaâcoub have never been studied and the phlebotomy fauna of the region remains unknown until now. Methods: Trapping was done using sticky traps once a month during the period of activity of sandfly from April to October. Results: A total of 3287 specimens of sandflies were collected. 8 species belonging to two genera Phlebotomus (94.3%) and Sergentomyia (5.7%). The study of sex ratio showed an advantage of males to females for all species. However, for the species S. falax, S. antennata, S. minuta we have not collected females. The highest sex ratio was determined for Ph. Perniciosus and lowest among S. dreyfussi. The results show a difference in the distribution of species between different localities. Conclusion: it was possible to distinguish two major entities; a dominant sub-genre Phlebotomus and Paraphlébotomus, responsible for the cutaneous form in the center and northwest of the province, and a sub-genre dominated Larroussius entity responsible for the visceral form the northeast of the province with a small entity in the south-eastern province. The results of this study will help undoubtedly health authorities to establish appropriate monitoring and anti-vectorial control measures.